Unique ultrastructural organization of human rod photoreceptors - Tylor R. Lewis; Natalia V. Klementieva; Sebastien Phan; Carson M. Castillo; Keun-Young Kim; Lauren Y. Cao; Mark H. Ellisman; Vadim Y. Arshavsky; Oleg Alekseev (Communications Biology)
Abstract Rod and cone photoreceptor cells are specialized neurons responsible for transforming the information reaching the eyes in the form of photons into the language of neuronal activity. Rods are the most prevalent photoreceptor type, primarily responsible for light detection under conditions of limited illumination. Here we demonstrate that human rods have a morphological organization unique among all described species, whereby the cell soma extends alongside the light-sensitive outer segment compartment to form a structure we have termed the “accessory inner segment.” These structures have two striking features: they are reinforced by a massive microtubular cytoskeleton and contain electron-dense adhesions that mediate their attachment to outer segments. Given that the spacing of human rod photoreceptors is sparser than in most other species, the accessory inner segment likely provides mechanical support to the closely apposed outer segment. This discovery expands our understanding of the human retina and directs future studies of human photoreceptor function in health and disease.